Sagnacov pojav - Strnad, Janez (Obzornik za matematiko in fiziko, 2013)
The centenary of the Sagnac experiment is a viable excuse for a brief discussion of ring interferometers. A. A. Michelson with collaborators observed with ring interferometer the rotation of the Earth. Later on laser ring interferometers and fiber ring interferometers were developed. In a hundred years the measuring techniques experienced and exceptional development. Currently the angular velecity of the Earth is monitored.
Keywords: fizika; physics; krožni iterferometri; Sagnacov poskus; kotna hitrost Zemlje